2022
DOI: 10.5114/jcb.2022.120765
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different treatment protocols on achieved radiation doses of high-dose-rate brachytherapy for locally advanced cervical cancer: a comparison between 2 fractions in 1 application and separate applications for each fraction

Abstract: Purpose: To compare radiation doses achieved by image-guided brachytherapy for locally advanced cervical carcinoma implemented with two different protocols.Material and methods: Medical records of 117 patients with locally advanced cervical carcinoma treated with brachytherapy from 2009 to 2018 at our institution were retrospectively reviewed. All patients had received previous external beam radio/chemotherapy. We performed magnetic resonance image-guided adaptive high-dose-rate brachytherapy delivered by intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Interstitial BT is usually done as out-patient with multiple insertions, or in-patient with multiple insertions, and least commonly as in-patient with a single insertion [ 15 ]. A study comparing single application with multiple insertions showed that single insertion had lower costs while maintaining similar local control and toxicity [ 16 ]. Correspondingly, during the COVID-19 pandemic, some centers shifted to single application to ease anesthesia and in-patient strain [ 17 ].…”
Section: Purposementioning
confidence: 99%
“…Interstitial BT is usually done as out-patient with multiple insertions, or in-patient with multiple insertions, and least commonly as in-patient with a single insertion [ 15 ]. A study comparing single application with multiple insertions showed that single insertion had lower costs while maintaining similar local control and toxicity [ 16 ]. Correspondingly, during the COVID-19 pandemic, some centers shifted to single application to ease anesthesia and in-patient strain [ 17 ].…”
Section: Purposementioning
confidence: 99%